The key roles of complement and tissue factor in Escherichia coli‐induced coagulation in human whole blood. (2nd August 2015) - Landsem, A.; Fure, H.; Christiansen, D.; Nielsen, E. W.; Østerud, B.; Mollnes, T. E.; Brekke, O. L.
Summary The complement system and the Toll‐like (TLR) co‐receptor CD14 play important roles in innate immunity and sepsis. Tissue factor (TF) is a key initiating component in intravascular coagulation in sepsis, and long pentraxin 3 (PTX3) enhances the lipopolysaccharide (LPS)‐induced transcription of TF. The aim of this study was to study the mechanism by which complement and CD14 affects LPS‐ and Escherichia coli (E. coli)‐induced coagulation in human blood. Fresh whole blood was anti‐coagulated with lepirudin, and incubated with ultra‐purified LPS (100 ng/ml) or with E. coli (1 × 107/ml). Inhibitors and controls included the C3 blocking peptide compstatin, an anti‐CD14 F(ab′)2 antibody and a control F(ab′)2. TF mRNA was measured using quantitative polymerase chain reaction (qPCR) and monocyte TF surface expression by flow cytometry. TF functional activity in plasma microparticles was measured using an amidolytic assay. Prothrombin fragment F 1+2 (PTF1.2) and PTX3 were measured by enzyme‐linked immunosorbent assay (ELISA). The effect of TF was examined using an anti‐TF blocking antibody. E. coli increased plasma PTF1.2 and PTX3 levels markedly. This increase was reduced by 84–>99% with compstatin, 55–97% with anti‐CD14 and > 99% with combined inhibition (P < 0·05 for all). The combined inhibition was significantly (P < 0·05) more efficient than compstatin and anti‐CD14 alone. The LPS‐ and E. coli–induced TF mRNA levels, monocyte TF surface expression and TF functional activity were reduced by > 99% (P < 0·05) with combined C3 and CD14 inhibition. LPS‐ and E. coli–induced PTF1.2 was reduced by 76–81% (P < 0·05) with anti‐TF antibody. LPS and E. coli activated the coagulation system by a complement‐ and CD14‐dependent up‐regulation of TF, leading subsequently to prothrombin activation.